Effects of G6pc2 Deletion on Body Weight and Cholesterol in Mice - Boortz, Kayla A. (J Mol Endocrinol, 2017)
Genome wide association study (GWAS) data have linked the G6PC2 gene to variations in fasting blood glucose (FBG). G6PC2 encodes an islet-specific glucose-6-phosphatase catalytic subunit that forms a substrate cycle with the beta cell glucose sensor glucokinase. This cycle modulates the glucose sensitivity of insulin secretion and hence FBG. GWAS data have not linked G6PC2 to variations in body weight but we previously reported that female C57BL/6J G6pc2 knockout (KO) mice were lighter than wild-type littermates on both a chow and high fat diet. The purpose of this study was to compare the effects of G6pc2 deletion on FBG and body weight in both chow fed and high fat fed mice on two other genetic backgrounds. FBG was reduced in G6pc2 KO mice largely independently of gender, genetic background or diet. In contrast, the effect of G6pc2 deletion on body weight was markedly influenced by these variables. Deletion of G6pc2 conferred a marked protection against diet-induced obesity in male mixed genetic background mice whereas in 129SvEv mice deletion of G6pc2 had no effect on body weight. G6pc2 deletion also reduced plasma cholesterol levels in a manner dependent on gender, genetic background and diet. An association between G6PC2 and plasma cholesterol was also observed in humans through electronic health record-derived phenotype analyses. These observations suggest that the action of G6PC2 on FBG is largely independent of the influences of environment, modifier genes or epigenetic events whereas the action of G6PC2 on body weight and cholesterol are influenced by unknown variables.